Comorbidity and Fatality Among Covid Patients: A Hospital Based-Retrospective Cohort Study - Yeni Kartika Sari; Thatit Nurmawati; Joko Ivnu Santoso; Maratus Sholichah Fitriah Hajar Kusnianto (Journal of Ners and Midwifery, 2023)
People with comorbid diseases have a high risk of contracting COVID-19, because the immune system has decreased, thus increasing the risk of transmission of COVID-19 and even potentially increasing the risk of fatality. This study aimed to determine the comorbidity and mortality among COVID-19 confirmed cases during May to September, 2021. The study was a retrospective cohort with secondary data from the COVID-19 with in Hospital report from May to September, 2021, with a total sample of 178. We extracted demographic and clinical data, including hospital outcomes (discharge or death). The result of the research showed that the respondents separated in to two groups, half of them are patients with comorbidity (89 patients) and the rest are patients non comorbidity. From 89 patients with comorbidity, 62 % were died and 38 % were discharged. The most comorbidites were 67,4% diabetes mellitus, 33% hypertension. The fatality rate of COVID-19 patients was 34% devided to 61,8% were comorbidity patients and 5,5% were non comorbidity. The comorbidity related to fatality rate of COVID-19 patient’s (p=0.000). It is important for society to avoid and control comorbid factors of COVID-19